Semantic and Syntaxic Analysis of the 2024 Presidential Debate: A Case Study of Van Dijk's Approach - Salvia Micca; Ririn Rahayu; Masithah Mahsa (SAINTIS Publishing, 2025)
This study aims to analyze the semantics and syntax of Teun A. van Dijk's model in the third presidential debate of the 2024 presidential candidates. This study uses a descriptive qualitative approach. The data in this study are oral discourses in the 2024 presidential debate uploaded by the Indonesian General Elections Commission (KPU RI) YouTube channel with the theme of security, defense, globalization, international relations, geopolitics, and foreign policy. The data source in this study was obtained from the KPU RI YouTube channel with the title